Cyclic single drop square wave polarography at spherical electrodes - the reversible case - Ramalay, Louis; Tan, Wee Tee (N R C Research Press, 1987)
The influence of electrode sphericity and the results of sweep reversal are examined for square wave voltammetry and the square wave polarography in which an entire polarogram is obtained on a single drop. An expanding sphere treatment obtained by adding a spherical correction to expanding plane theory gives the best fit to the experimental data. Amalgam forming reactions fit the simple theory developed to a lesser extent than other reactions, especially on the reverse sweep. The shape of the differential polarogram is not significantly affected by sphericity and the reverse peak potential is approximately equal to the forward peak potential. Small differences in these potentials are due to the distortion of the square wave by the stairstep used for the sweep and the distortion of the polarogram due to drop growth. The ratio of the forward and reverse peak currents depends on the phasing of the square wave and stairstep in all cases and on other parameters for a growing drop.